2017
DOI: 10.5005/jp-journals-10024-2082
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Dental Anomalies in Odisha Population: A Panoramic Radiographic Study

Abstract: Aim:The aim of this study was to evaluate the prevalence of dental anomalies (DAs) in Odisha population using panoramic radiographs. Materials and methods:In this study, 1,080 panoramic radiographs were evaluated for DAs. Dental records were reviewed for diagnostic confirmation. Anomalies related to the shape, size, position of teeth, and number of roots (supernumerary roots) were evaluated. Results:The study results showed the prevalence of DAs to be 35.27%. The most prevalent was dilaceration, which was seen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 15 publications
(16 reference statements)
2
14
0
Order By: Relevance
“…In a similar study conducted on Iranian population, a similar prevalence of 47.5% ( Dalili et al, 2012 ) was found. However, higher prevalence (56.9%) was reported in Brazilian population( Goncalves-Filho et al, 2014 ) a lower prevalence was found in Odisha state in India ( Goutham et al, 2017 ). These differences could be attributed to the regional and racial variations of the studied population.…”
Section: Discussionmentioning
confidence: 86%
“…In a similar study conducted on Iranian population, a similar prevalence of 47.5% ( Dalili et al, 2012 ) was found. However, higher prevalence (56.9%) was reported in Brazilian population( Goncalves-Filho et al, 2014 ) a lower prevalence was found in Odisha state in India ( Goutham et al, 2017 ). These differences could be attributed to the regional and racial variations of the studied population.…”
Section: Discussionmentioning
confidence: 86%
“…[ 2 3 ] This results in a tooth with a bifid crown, while the total number of teeth is normal. [ 4 ] In the present article, a case of germination in mandibular third molar has been reported; it is a rare entity by itself, showing the atypical coronal and radicular morphology.…”
Section: Introductionmentioning
confidence: 71%
“… 9 The prevalence was found to be 16.48% in the other study with female prediliction. 4 The variations in result is mainly due to sampling technique, ethnic diversity, and different inclusion criteria. The prevalence in international studies was found to be 5.29% in southeastern Iranian population 11 and 0.18% in French population.…”
Section: Discussionmentioning
confidence: 99%
“…The secondary variations may be due to environmental factors, such as changes in genetic composition, prenatal and postnatal events like any change occurring during the mineralization, or maturation process of the tooth that will affect the mineralized component like enamel, dentin, or the cementum. 4 The anomalies affecting the morphology of teeth comprise of talon cusp, dens invaginatus, dens evaginatus, gemination, fusion, root dilacerations, taurodontism, concrescence, and supernumerary roots. The most commonly seen anomaly related to shape is fused teeth.…”
Section: Introductionmentioning
confidence: 99%